A National Assessment of the Potential Linkage between Soil, and Surface and Groundwater Concentrations of Phosphorus1. (14th July 2015) - McDowell, R.W.; Cox, N.; Daughney, C.J.; Wheeler, D.; Moreau, M.
Abstract A meta‐analysis of three national databases determined the potential linkage between soil and surface and groundwater enrichment with phosphorus (P). Soil P was enriched especially under dairying commensurate with an increase in cow numbers and the tonnage of P‐fertilizers sold. Median P concentrations were enriched in surface waters receiving runoff from industrial and dairy land uses, and in groundwater beneath dairying especially in those aquifers with gravel or sand lithology, irrespective of groundwater redox status. After geographically pairing surface and groundwater sites to maximize the chance of connectivity, a subset of sites dominated by aquifers with gravel and sand lithology showed increasing P concentrations with as little as 10 years data. These data raise the possibility that groundwater could contribute much P to surface water if: there is good connectivity between surface and groundwater, intensive land use occurs on soils prone to leaching, and leached‐P is not attenuated through aquifers. While strategies are available to mitigate P loss from intensive farming systems in the short‐term, factors such as enriched soils and slow groundwater may mean that despite their use, there will be a long‐term input (viz. legacy), that may sustain surface water P enrichment. To avoid poor surface water quality, management and planning may need to consider the connectivity and characteristics of P in soil‐groundwater‐surface water systems.